2002
DOI: 10.1053/seiz.2001.0662
|View full text |Cite
|
Sign up to set email alerts
|

Clinical expression and EEG features of patients with juvenile myoclonic epilepsy (JME) from North India

Abstract: We aimed to characterize the clinical profile, EEG features and response to treatment of juvenile myoclonic epilepsy (JME) patients. We studied 103 JME probands with a standard protocol recording age of onset, type, frequency of seizures, EEG data, detailed family history and response to treatment in a superspeciality university hospital in New Delhi. The mean age of onset of disease was 14.01 +/- 3.14 years with a male to female ratio of 1.19 : 1. The myoclonic jerks were present in all the probands, generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 30 publications
6
41
0
9
Order By: Relevance
“…Many patients do not mention about myoclonic jerks as they usually do not found as significant (Mehndiratta and Aggarwal, 2002). Our case also did not mentioned from myoclonic jerks, before admitted to our inpatient clinic.…”
Section: Discussionmentioning
confidence: 45%
“…Many patients do not mention about myoclonic jerks as they usually do not found as significant (Mehndiratta and Aggarwal, 2002). Our case also did not mentioned from myoclonic jerks, before admitted to our inpatient clinic.…”
Section: Discussionmentioning
confidence: 45%
“…7 At 60.7% incidence of myoclonic among males is comparable to other studies have shown higher incidence in males, few studies showed female preponderance pooled analysis of all studies may yield a good result. [12][13][14] Among 75 patients 52 patients were on valproate, 6 on carbamazepine, 3 patients on phenytoin, and 5 were on leviteracetam, 9 requiring multiple anti-epileptic drugs. Among patients on valproate therapy 88.6% had good response which was comparable most of studies on drug response in myoclonic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürdeki geniş hasta çalışmalarından oluşan birçok çalışmada cinsiyet dağılımı bizim sonuçlarımız-dan (2.7:1) farklı olarak eşit dağılım (1:1) olduğu bildirilmiştir. [4][5][6] Çelik ve ark.nın JME'li hastalarının klinik ve EEG özellik-lerini değerlendirdikleri bir çalışmada kadın/erkek oranını bizim sonuçlarımıza benzer şekilde bulmuşlardır. Ayrıca fotosensitif hasta sayısı da benzer şekilde literatürde bildirilenden düşük sayıdadır.…”
Section: Discussionunclassified
“…Mehndiratta'nın Hindistan'da yaptığı geniş hasta serili çalışmada hastaların yalnızca %16.50'sinde sadece miyoklonik sıçramalar görü-lürken en sık miyokloni ve JTKN birlikteliği (%71.84) görül-düğü bildirilmiştir. [4] Türkiye'den Gömceli ve ark., yaptıkları bir çalışmada JME hastalarının %11.8'inde sadece miyokloni görüldüğü, en sık miyokloni ve JTKN birlikteliğinin (%60) görüldüğünü bildirmişlerdir. [6] Bizim çalışmamızda tedavi altındaki hiçbir hastanın tek başına miyokloni nedeniyle doktora başvurmadığı, JTKN nedeniyle tetkik edildikten sonra tanı aldıkları belirlendi.…”
Section: Discussionunclassified
See 1 more Smart Citation